Pengaruh Belanja Daerah Terhadap Indeks Pembangunan Manusia Di Provinsi Papua Periode 2011 Hingga 2013 Dalam Perspektif Ekonomi Islam - Firly Dwitya Kamilia; Tika Widiastuti (Universitas Airlangga, 2016)
The aim of this study was to determine the effect of education spending and healthspending on the Human Development Index (HDI) in Papua Province period 2011-2013. Themethod used is quantitative method with panel data regression techniques. The data used issecondary data by collecting data annual financial statements Papua Province in theperiod 2011-2013 which includes education and health spending data across district in theprovince of Papua.Panel data regression conducted showed that spending on education (X1) positive andsignificant impact on the human development index in province of Papua and healthspending (X2) has no effect on the human development index in Papua as well as spendingon education and helath spending simultaneously affect the human development index inPapua Province 2011-2013.